Effects of the herbicide glyphosate on biological attributes of Alpaida veniliae (Araneae, Araneidae), in laboratory - Benamú, Marco Antonio (2010)
In the past decades there has been increasing interest in the study of arthropod predators as effective potential natural enemies to be used in the biological control of agricultural pests. In Argentina, transgenic soybean crops (Round-up Ready, RR) are inhabit by many spider species, some of them in high abundance, being indicative of an import potential for pest predation. This crop is associated with the use of glyphosate, a broad-spectrum herbicide, with low environmental impact, even though since the 80's, several negative effects have been deeply documented on mammals, fishes, amphibians, snails, earthworms, insects, etc. Nowadays, the effects on arthropod physiology, behavior and life history traits as end-points in ecotoxicological evaluations are being recognized. In transgenic soybean crops of Buenos Aires province (Argentina), Alpaida veniliae (Araneae, Araneidae) is one of the most abundant orb web weaver spiders. The purpose of this study was to address the effects of glyphosate on some biological attributes of A. veniliae, in laboratory. Results of this study showed no lethal direct effects of Glifoglex on this spider, but it is the first report in literature about sublethal effects of this herbicide on a spider's biological attributes. Negative effects on prey consumption, web building, fecundity, fertility and developmental time of progeny were observed. Although sublethal effects have received less attention than direct lethal effects, they are relevant from an ecological point of view, since the reduction of the arthropod performance may create risks to arthropod biodiversity conservation in agroecosystems.